Potential contribution of GST-T1 and GST-M1 polymorphisms in the onset of hepatic steatosis: from radiological to molecular and medico-legal analyses - Cianci, Vincenzo; Mondello, Cristina; Baldino, Gennaro; Spatari, Giovanna; Alibrandi, Angela; Cianci, Alessio; Cracò, Annalisa; Gualniera, Patrizia; Asmundo, Alessio; Gaeta, Michele; Giorgianni, Concetto; Sapienza, Daniela (Frontiers in Gastroenterology, 2024)
IntroductionNon-alcoholic fatty liver disease (NAFLD) is the most prevalent form of chronic liver disease in the world, and it is characterized by an excessive hepatic fat accumulation in more than 5% of hepatocytes documented by histology in the absence of alcohol consumption. It is a multifactorial pathology, where genetic component plays a fundamental role: the loss-of-function polymorphisms of genes coding for glutathione S-transferases would predispose to the pathology onset, also in the absence of other risk factors. The aim of the study was to evaluate the relation between the “NULL” GST-T1 and GST-M1 polymorphisms and the onset of NAFLD.MethodsA group of 117 “apparently healthy” Caucasian volunteers, selected from a larger population through the analysis of previously administered short questionnaires, underwent both magnetic resonance imaging-proton density fat fraction (MRI-PDFF) and buccal swabs: the aim was to identify the possible presence of hepatic steatosis and of the aforementioned “NULL” polymorphisms of interest.ResultsA statistically significant association between the GST-T1 and GST-M1 “NULL” genotypes and the probability of developing NAFLD has been identified. In particular, the GST-T1 “NULL” genotype has been associated with a greater probability of developing steatosis in early age, while the GST-M1 “NULL” genotype seems to increase the risk of developing a higher grade of steatosis. No statistically significant correlations between the “NULL” genotype and sex have been detected.DiscussionAmong the numerous risk factors capable of predisposing to NAFLD onset and progression, the genetic factors seem to play an important role. In particular, GST-T1 and GST-M1 “NULL” polymorphisms would appear to acquire even greater importance, as their loss of function results in an increase of oxidative stress. At high concentrations, ROS can determine oxidative modifications of cellular macromolecules, such as lipids, determining their accumulation into hepatocytes. The study also highlighted the importance of MRI-PDFF for hepatic steatosis diagnosis: this method allows the acquisition of data comparable to those of conventional biopsy; however, it permits the entire liver parenchyma to be visualized.ConclusionA statistically significant correlation between the presence of GST-T1 and GST-M1 “NULL” genotypes and the presence of hepatic steatosis has been found.